Gaussian Pell Numbers - Balamurugan, P.; Gnanam, A. (International Journal of Engineering and Technology, 2018)
Gaussian numbers means representation as Complex numbers. In this work, Gaussian Pell numbers are defined from recurrence relation of Pell numbers. Here the recurrence relation on Gaussian Pell number is represented in two dimensional approach. This provides an extension of Pell numbers into the complex plane.Â